2017
DOI: 10.1002/ejoc.201701073
|View full text |Cite
|
Sign up to set email alerts
|

On the Asymmetric Induction in Proline‐Catalyzed Aldol Reactions: Reagent‐Controlled Addition Reactions of 2,2‐Dimethyl‐1,3‐dioxane‐5‐one to Acyclic Chiral α‐Branched Aldehydes

Abstract: Reagent stereocontrol in the proline‐catalyzed aldol reaction of 2,2‐dimethyl‐1,3‐dioxane‐5‐one 1 with chiral aldehydes has been investigated. Synthetically useful levels of diastereoselectivity could be achieved in reactions with acyclic chiral α‐oxy and α‐amino aldehydes in both matched and mismatched cases. By using this reaction as a key step, two medicinally relevant azasugars, 1‐deoxy‐galactonojirimycin (9) and 2,5‐dideoxy‐2,5‐imino‐d‐altritol (10), were efficiently synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Notably, when this reaction was repeated in CH 2 Cl 2 or DMSO, the yield was significantly lower. The l -proline-catalyzed aldol reaction between ( S )-2-Cbz-aminopentanal and dioxanone yielded the corresponding anti-aminohydrin as the sole product, and both l - and d -proline-catalyzed aldol reactions of ( S )- N -Cbz prolinal (Supplementary Schemes 1 and 2 ) each gave single products without epimerization of the α-stereocenter, further confirming that α-aminoaldehydes do not racemize under these reaction conditions ( k rac << k aldol ) 47 . We also examined the l -proline-catalyzed aldol reaction of (±)-2-phenylpropanal and dioxanone 13 (Supplementary Scheme 3 ), which afforded an equal mixture of syn- and anti- diastereomers again suggesting k rac << k aldol .…”
Section: Resultsmentioning
confidence: 66%
“…Notably, when this reaction was repeated in CH 2 Cl 2 or DMSO, the yield was significantly lower. The l -proline-catalyzed aldol reaction between ( S )-2-Cbz-aminopentanal and dioxanone yielded the corresponding anti-aminohydrin as the sole product, and both l - and d -proline-catalyzed aldol reactions of ( S )- N -Cbz prolinal (Supplementary Schemes 1 and 2 ) each gave single products without epimerization of the α-stereocenter, further confirming that α-aminoaldehydes do not racemize under these reaction conditions ( k rac << k aldol ) 47 . We also examined the l -proline-catalyzed aldol reaction of (±)-2-phenylpropanal and dioxanone 13 (Supplementary Scheme 3 ), which afforded an equal mixture of syn- and anti- diastereomers again suggesting k rac << k aldol .…”
Section: Resultsmentioning
confidence: 66%
“…However, there were contradictory reports regarding double asymmetric synthesis in proline‐ catalyzed dioxanone addition to chiral aldehydes: whereas it was generally accepted that ( R )‐Pro/( S )‐aldehyde (or ( S )‐Pro/( R )‐aldehyde) constitute a matched pair (in line with calculations presented above), one report claimed reverse stereochemical matching of reactants ( i. e ., ( S )‐Pro/( S )‐aldehyde) and low reactivity in mismatched case [25c] . Subsequent study found that a range of α‐substituted (as well as α,β‐disubstituted) aldehydes 8 a – e (containing a suitably protected nitrogen substituent at α‐ or β‐position, for consecutive reductive amination) can be used as acceptors, where the combination of ( R )‐Pro and ( S )‐aldehyde was a matched case [28] . In most of mismatched cases, reagent control provided synthetically useful levels of stereoselectivity, provided the α‐substituent is not part of a cyclic structure (see aldehyde 8 e , entry 5, where poor yield and low stereoselectivity are observed with).…”
Section: Organocatalyzed Aldolization/reductive Amination As the Key Step In Synthesis Of Iminosugarsmentioning
confidence: 99%
“…At subinhibitory concentrations, DGJ acts as a pharmacological chaperon for mutated α‐galactosidase A, thus allowing it to escape from the quality control in endoplasmic reticulum and become active in glycoprotein processing [30] . This compound, clinically approved under commercial name Galafold ® (generic: migalastat), is synthesized according to Scheme 3 [28] . ( R )‐Proline‐catalyzed aldol addition of dioxanone 1 to isoserinal 8 b provided aldol 10 b with 13 : 1 selectivity; however, the purification of the required isomer is greatly facilitated by the fact that it spontaneously cyclizes into hemiaminal 12 , whereas the minor diastereoisomer does not (this appears to be is a general feature of Cbz‐ and Boc‐protected 3‐ and 4‐amino‐substituted aldols).…”
Section: Organocatalyzed Aldolization/reductive Amination As the Key Step In Synthesis Of Iminosugarsmentioning
confidence: 99%
“…A peculiar case was represented by ionic liquids (ILs) [67][68][69][70][71][72], which allowed in a few cases to decrease the catalyst loading (up to 1 mol%) and, during the work-up, to confine proline in a separate phase, enabling a simple product isolation and the reuse of the catalytic system. In recent literature, attempts are reported where proline is used in acetone/CHCl 3 mixtures [73], in DMF at 4 • C (a condition that often requires several days) [74], in tert-butyl methyl ether (MTBE) [75], in deep eutectic solvents [76,77], or under solvent-free conditions, with [78][79][80] or without [81] the ball milling approach. However, many issues associated with the use of proline remain unsolved and polar aprotic solvents are characterized by several undesirable features (toxicity, high production cost, high environmental impact, difficult product recovery) [82][83][84].…”
Section: Introductionmentioning
confidence: 99%